Tyre model development using co-simulation technique for helicopter ground operation. (December 2014) - Wang, Yun; Blundell, MV; Woodand, G; Bastien, C
This paper describes the development of a new aircraft tyre model applied using a co-simulation approach for the multibody dynamic simulation of helicopter ground vehicle dynamics. The new tyre model is presented using a point follower approach that makes a novel contribution to this area by uniquely combining elements of two existing tyre models used by the aircraft industry, namely the NASA R64 model developed by Smiley and Horne and the Engineering Sciences Data Unit (ESDU) Mitchell tyre model. Before the tyre model was used with a full helicopter model, a virtual tyre test rig was used to examine the tyre and to predict the tyre forces and moments for a range of tyre states. The paper concludes by describing the successful application of the new tyre model with a full helicopter model and the simulation of representative landing, take-off and runway taxiing manoeuvres. The predictive capability of the model is demonstrated to show the open-loop ground vehicle dynamics response of the helicopter and also the ground load predictive capability for the distribution of loads through the tyres, wheels and landing gears.